Comment : Scientific linguistics. (21st March 2017) - Allen, Frank; Davies, Geoff; McDowell, Alex
Abstract: In response to Brian Clegg's feature article "Speaking a different language" (February pp34–37), in which he suggests that a good science communicator anticipates the kind of questions the audience will want to have answered.